Hunting ants (Ectatomminae y Ponerinae) in dry forest fragments and their matrix (Tolima, Colombia) - YARA-O., CLAUDIA; REINOSO-F., GLADYS (Revista Colombiana de Entomología, 2012)
The richness, abundance and composition of hunting ants in three fragments of tropical dry forests in the northern region of Tolima, Colombia and their matrices were assessed; in addition, three scrub patches of shrub were included due to their high frequency in the landscape. Two samplings were carried out between May to June and October to November 2011. In each habitat, a linear 150 m transect was established in which pitfall traps were installed and 1m2 leaf-litter samples were extracted in mini-Winkler sacks were extracted. The 17 hunting ant species of Ectatomminae and Ponerinae found represent 44.7% of all the species reported for Tolima State. There significative differences in richness: 13 species were found in forests, seven in the matrix and 10 in the scrub patches and 17.17, 7, 11.94 species for forest, matrix ans scrub for estimated richness Chao 2. Locally, the species richness between forests and their matrices differed significantly only in the Centro Universitario Regional del Norte (CURN-UT), while the species composition was different in all sites and, but similar between forests and shrub patches. It is possible that the conversion of natural habitats into agricultural land areas become a modifying factor of the structure of hunting ants communities, that although in some sites the species richness is similar in forests and matrices, the species composition differs between them and in this way, the community responds to such changes.